Efficacy and Safety of Probiotics in Irritable Bowel Syndrome: A Systematic Review and Meta-Analysis - Li, Bing (Front Pharmacol, 2020)
BACKGROUND: Irritable bowel syndrome is a functional gastrointestinal disease. Evidence has suggested that probiotics may benefit IBS symptoms. However, clinical trials remain conflicting. AIMS: To implement a systematic review and meta-analysis of clinical trials regarding the efficacy and safety of probiotics for IBS patients. METHODS: We searched for relevant trials in Medline(1966 to Jan 2019), Embase(1974 to Jan 2019), the Cochrane Central Register of Controlled Trials(up to Jan 2019), the ClinicalTrials.gov trials register(up to Jan 2019), and Chinese Biomedical Literature Database(1978 to Jan 2019). Risk ratio (RR) and a 95% confidence interval (CI) were calculated for dichotomous outcomes. Standardized mean difference (SMD) and 95% CI were calculated for continuous outcomes. RESULTS: A total of 59 studies, including 6,761 patients, were obtained. The RR of the improvement or response with probiotics versus placebo was 1.52 (95% CI 1.32–1.76), with significant heterogeneity (I(2) = 71%, P < 0.001). The SMD of Probiotics in improving global IBS symptoms vs. Placebo was -1.8(95% CI -0.30 to -0.06), with significant heterogeneity (I(2) = 65%, P < 0.001). It was impossible to draw a determinate conclusion. However, there were differences in subgroup analyses of probiotics type, dose, treatment duration, and geographic position. Probiotics seem to be safe by the analysis of adverse events(RR = 1.07; 95% CI 0.92–1.24; I(2) = 0, P = 0.83). CONCLUSION: Probiotics are effective and safe for IBS patients. Single probiotics with a higher dose (daily dose of probiotics ≥10(10)) and shorter duration (< 8 weeks) seem to be a better choice, but it still needs more trials to prove it.